RUSSIA INTERNATIONAL RELATIONS THEORY: WHAT SHOULD IT BE LIKE? - Andrei Tsygankov (Сравнительная политика, 2015)
Russian IR theory faces many difficulties including underdevelopment of empiric research and overall abstract approach of theoretic studies. The article suggests to reconsider the development of the Russian IR theory in order to face the new economic, political and ethno-cultural challenges. The formation of Russian IR theory is still underway, and it is characterized by contradictions and the presence of mutually exclusive universalist and isolationist approaches. The article raises the question of overcoming the extreme approaches in the IR theory through reducing the gap between the teaching of IR and Russian political thought. The article concludes that the development of IR in Russia requires deep knowledge of its intellectual roots, thus the study of the Russian political thought becomes the necessity.